The Superiority of the Language of the Qur'an from the Perspective of Balaghah Science - Ian Septiana (Tilawah: Journal of Al-Qur'an Studies, 2025)
Al-Quran is one of the kitab of Allah which was revealed to one of His prophets. Al-Qur'an is a kitab that Allah SWT sent down to the Prophet Muhammad SAW which at the same time made the Al-Quran as one of the greatest miracles of the Prophet SAW. The existence of the Al-Quran is still maintained until now. The kitab of the Quran contains very broad verses so that previous scholars explored the contents of the verses of the Quran with various disciplines, one of which is the science of balaghah. This study aims to determine the superiority of the language of the Quran in the perspective of balaghah science. The method used by the author in this study is a qualitative research method with an inductive approach, which then collects data through literature reviews, quotes, and analyzes data sources related to the subject matter. This journal seeks to explain the science of balaghah and its correlation with the kitab of the Quran and the superiority of the language of the Quran in the perspective of the science of balaghah.